Impact of charge carrier transport properties on conductivity-temperature dependence of gellan gum-LiCF3SO3 biopolymer electrolyte - Abdul Aziz, N. A.; M. Tarmizi, E. Z.; Razak, C. S. C.; Noor, I. M. (Sage Publications, 2022)
Charge carrier density, mobility and diffusivity are three important transport properties in determining the ionic conductivity as well as the performance of solid polymer electrolyte. In this work, biopolymer electrolytes samples were prepared using the solution casting method by complexing gellan gum with different concentrations of lithium trifluoromethanesulfonate (3–15 wt.%). The values of charge carrier concentration, mobility, and diffusivity for electrolyte samples were estimated by fitting the Nyquist plot with an equation developed based on electrical impedance spectroscopy. At room temperature, the optimum electrolyte conductivity is 1.29×10−8 Scm−1 at 6 wt.% salt concentration. This result was supported by the highest percentage of free ions, 31.45%, observed in the FTIR method. As the temperature increases, the ionic conductivity increases to the optimum value before dropping. The highest conductivity of each sample was obtained at different temperatures (80°C–90°C) using the impedance method, whereas the percentage area of free ions was highest at 80°C for all samples with FTIR analysis. Overall, the ionic conductivity of this system has been dominated by the carrier charge density. Results suggest that, under these experimental conditions, electrical impedance spectroscopy is suitable for evaluating the charge transport properties at low temperatures.